A atenção ao uso problemático de álcool na rede básica de saúde de um município do interior paulista : possibilidades e limites na percepção de gestores - Andrade, Andrea Santos de (2012)
The new structure of attention to the risky use, abuse and alcohol dependence in Brazil, was developed inside the resulting changes from the Psychiatric Reform. The current organization of the Brazilian health system has, among its guidelines, the units of primary care as the one of the access for users of health services. In this context, the Family Health Strategy has been identified as a distinguished field in the development of actions to identify and care alcohol dependents. Recent national policies that address the issue provide measures of comprehensive care to alcoholics, in addition to social, health and life harm reduction caused by abusive consumption of alcohol. Faced with the National Policy on Alcohol, it is questioned how policies have been put into practice by local health managers, as well as what the limits and possibilities of its implementation are. This qualitative study aimed to assess the perceptions of managers of the Department of Health, from a city of Sao Paulo State, which are responsible for health care services related to the subject, on the attention to the use, abuse and alcohol dependence. It was used as a background to this assessment, the reference of the Psychiatric Reform and the National Policy on Alcohol. To this end, it was also considered important to contextualize the municipality through consultation of documents and information given by the managers. To assess the perception of managers on the attention to the risky use, abuse and alcohol dependence in primary care, it was carried out semi-structured interviews with twelve of them. All ethical considerations were observed. Data were analyzed according to the content analysis, which is a thematic category proposed by Bardin. The assessment of interviews resulted in four themes: The thinking of managers on Alcohol Dependence Syndrome (ADS); Factors favoring the development of actions related to alcohol issues: from the potential to the implementation of actions; Fragility and limits for the development of actions related to alcohol issues; Tackling alcohol issues by the government: perceptions, expectations and suggestions. When reflecting on the managers opinions about alcoholism, it was evidenced strong influence on the model of the disease, and no association was found to the relevant question of its syndrome nature. From the analysis of the possibilities and limitations it can be clearly seen that the potentialities of the municipality are primarily related to municipal public administration, the municipal health department, in which stands the work of CAPS ad, and other social groups. As reported, the major fragilities are associated with the unpreparedness of the ones involved in the development of mental health services in primary care, including alcohol issues. It is also of great significance, the history of treatment based on psychiatric hospital models, which continues to have strong influence on the knowledge and practices particularly from family members and health workers, who still have some prejudice on the subject. When expressing their expectations for the effectiveness of actions, managers pointed out several suggestions highlighting the need for planning and evaluating actions with the implementation of practices based on care protocols and capacitating workers. It was finally observed that the city has been experiencing a process of change in care to the person making abusive use of alcohol, approaching the assumptions of the Psychiatric Reform and the National Policy on Alcohol. However, its implementation faces limitations in the cultural, historical, structural, social and political order. Thus, the developed practices are inserted in a field of tension where there are still two coexisting models: a psychosocial and a traditional, which slows down the process of changes.